2015
DOI: 10.1016/j.indcrop.2015.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory scale optimization of alkali pretreatment for improving enzymatic hydrolysis of sweet sorghum bagasse

Abstract: Sweet sorghum has been identified as a promising feedstock for biological conversion to fuels as well as other chemicals. The lignocellulosic stalk of sweet sorghum, called sweet sorghum bagasse (SSB) is a potential source of lignocellulosic biofuel. The primary goal of this study was to determine optimal alkali (lime : Ca(OH)2 and lye : NaOH) pretreatment conditions to obtain higher yield of total reducing sugar while reducing the lignin content for biofuel production from SSB. Biomass conversion and lignin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 33 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Meanwhile, the result of study conducted by Toquero & Bolado (2014) using wheat straw showed that alkali hydrothermal pretreatment removed 51% of acid insoluble lignin. These suggested that the performance of pretreatment for different types of lignocellulose could be differ widely depending on the composition of biomass and severity of pretreatment conditions, although under same chemical pretreatment (Umagiliyage et al, 2015). The weight loss of biomass caused by alkali hydrothermal pretreatment was the highest than those caused by other pretreatments used in this study.…”
Section: Effects Of Alkali Hydrothermal Pretreatment On Chemical Compmentioning
confidence: 75%
“…Meanwhile, the result of study conducted by Toquero & Bolado (2014) using wheat straw showed that alkali hydrothermal pretreatment removed 51% of acid insoluble lignin. These suggested that the performance of pretreatment for different types of lignocellulose could be differ widely depending on the composition of biomass and severity of pretreatment conditions, although under same chemical pretreatment (Umagiliyage et al, 2015). The weight loss of biomass caused by alkali hydrothermal pretreatment was the highest than those caused by other pretreatments used in this study.…”
Section: Effects Of Alkali Hydrothermal Pretreatment On Chemical Compmentioning
confidence: 75%
“…Glucose concentration (mg/g), xylose concentration (mg/g), the rate of saccharification [35] Potato peel residues t = 30-60 • C, pH = 5-8, substrate concentration 2-10% (w/v), and surfactant concentration 0-1% (v/v) Saccharification yield [30] Sweet sorghum bagasse t = 50 • C, pH = 4.8, τ = 48 h Total reducing sugars, morphological changes [27] Coffee pulp t = 30 • C, τ = 48 h Reducing sugars, total reducing sugars, glucose concentration [29] Coastal bermudagrass t = 55 • C, pH = 4.8, τ = 72 h Total reducing sugars, glucose yield, xylose yield [26] Switchgrass t = 55 • C, pH = 4.8, τ = 72 h Total reducing sugars, concentration of glucose and xylose [37] The appropriate design of combined alkaline pre-treatment and enzymatic hydrolysis allows to obtain high yields of monosugars in hydrolyzates, even close to theoretical ones. Additionally, low concentrations of substances acting as inhibitors are formed, which is beneficial during further fermentation process.…”
Section: Feedstock Investigated Parameters Response Referencementioning
confidence: 99%
“…Biomass conversion, lignin removal, morphological changes [27] Coffee pulp C NaOH = 0-8% w/v; C Ca(OH)2 = 0-8% w/v; t = 121 • C, τ = 16.5-33.4 min; S:L = 1:5 w/v…”
Section: Introductionmentioning
confidence: 99%
“…lignin. The content of cellulose, the most important component, was comparable to that of other feedstock commonly used for bioethanol production, e.g., 36.3% for corn stover [41], 36.9% for sweet sorghum bagasse [33], 35.8% for rice straw [42], and 38.7% for wheat straw [43].…”
Section: Chemical Composition Of Raw and Pretreated Jerusalem Artichomentioning
confidence: 67%